2020
DOI: 10.1186/s12891-020-03581-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of pain and non-steroid anti-inflammatory drug use in collegiate athletes in the United States

Abstract: Background: Although athletic endeavours are associated with a high amount of physical stress and injury, the prevalence of pain is underreported in the sports medicine literature with only a few studies reporting pain on collegiate athletes or exploring sex difference of pain. Impact of pain on athlete availability, training and performance can be mitigated when key epidemiological information is used to inform adequate pain management strategies. This study aims to 1) provide an epidemiological profile of se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
(59 reference statements)
0
9
0
1
Order By: Relevance
“…The adverse consequences and side effects of NSAIDs are often underestimated [24,25]. They pose a high risk of AKI in people who use them without professional consultation, including athletes and older adults, as well as in long-term users [15,16,26,88].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adverse consequences and side effects of NSAIDs are often underestimated [24,25]. They pose a high risk of AKI in people who use them without professional consultation, including athletes and older adults, as well as in long-term users [15,16,26,88].…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs are commonly consumed as a fever reducers and analgesics, and because of their versatile effects, their daily use has become common [24]. Because athletes frequently experience physical stress and injuries, they might use painkillers to relieve discomfort [25]. Nevertheless, the adverse consequences and side effects of most of these drugs are underestimated [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make meaningful comparisons between sports, sport played was collapsed into collision, field and court sport, overhead, and individual. 27 …”
Section: Methodsmentioning
confidence: 99%
“…7 One study indicated that 46% of National Collegiate Athletic Association (NCAA) female athletes and 38% of NCAA male athletes who were experiencing injury-related pain were taking non-steroidal anti-inflammatory drugs (NSAIDs). 8 Among them, 70% of female athletes had purchased the NSAIDs themselves, versus 61% of male athletes, suggesting that they might not be part of their medical record or known by the medical staff. Another study reported that 62% of collegiate athletes use non-prescription drugs for injury-related pain management.…”
Section: Introductionmentioning
confidence: 99%